Legal change in post-communist states : progress, reversions, explanations - Solomon, Peter H.; Gadowska, Kaja (Soviet and post-Soviet politics and society, 2019)
This book-written by a team of socio-legal scholars-covers developments in legal institutions and the role of law in public administration across the former Soviet Union and Eastern Europe. It deals with both institutions such as courts and police and accountability to law in public administration, including anticorruption activities.